Analisis Komentar Warganet di X tentang Pernyataan Arifah Fauzi terkait Pemindahan Gerbong Wanita - Angelia Malika; Roma Kyo Kae Saniro; M. Aliffio Arya Putra; Afiya Ramadhani Juiza; M. Ibnu Jiwa Saputra; Rasya Triansyah; Aurenza Triazdy; Ferdinand Sundapa (Journal of Media and Communication | E-ISSN : 3063-9581, 2026)
This study aims to identify the nature of public responses, analyze the language used in comments, and examine their alignment with the values of Pancasila in digital communication. The subject of this study is netizens’ comments on the X platform regarding a statement by the Minister of Women’s Empowerment and Child Protection, Arifah Fauzi, concerning the proposal to move women-only carriages to the middle of the train following a train accident in East Bekasi in April 2026. This study employs a qualitative method with a document analysis approach. The data sources consist of 20 netizen comments on posts from the @MafiaWasit and @MiskinTV_ accounts on the X platform, collected through observation and documentation. This study is expected to serve as a useful reference for research on digital communication and the evaluation of the application of language ethics on social media. The results indicate that the majority of netizens reject this proposal. The language used includes criticism, sarcasm, and rude remarks. These findings suggest that communication ethics and the application of Pancasila values on social media remain relatively low.